2018
DOI: 10.3389/fpls.2018.01288
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Molecule Hydrogen Sulfide Improves Seed Germination and Seedling Growth of Maize (Zea mays L.) Under High Temperature by Inducing Antioxidant System and Osmolyte Biosynthesis

Abstract: Hydrogen sulfide (H2S) is a novel type signaling molecule in plants. Seed germination is a key stage of life cycle of plants, which is vulnerable to environmental stress including high temperature. However, under high temperature stress, whether pre-soaking of maize seeds with NaHS (a H2S donor) could improve seed germination and seedling growth and the possible mechanisms are not completely clear. In this study, maize seeds pre-soaked with NaHS enhanced germination percentage, sprout length, root length, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 58 publications
(101 reference statements)
2
38
0
5
Order By: Relevance
“…When seeds are germinated in non-optimal conditions there is a positive correlation between ROS scavenging ability through antioxidant systems and germination rate. For example, among only recent studies, seed antioxidant enzyme activities have been demonstrated to increase in response to high temperature and drought stress [43,80], low temperature [81], salt stress [82,83] or mutagen agents [38]. In those cases, the activation of antioxidant enzymes is necessary to prevent excessive ROS accumulation and related oxidative damage.…”
Section: Ros Production In Seedsmentioning
confidence: 99%
“…When seeds are germinated in non-optimal conditions there is a positive correlation between ROS scavenging ability through antioxidant systems and germination rate. For example, among only recent studies, seed antioxidant enzyme activities have been demonstrated to increase in response to high temperature and drought stress [43,80], low temperature [81], salt stress [82,83] or mutagen agents [38]. In those cases, the activation of antioxidant enzymes is necessary to prevent excessive ROS accumulation and related oxidative damage.…”
Section: Ros Production In Seedsmentioning
confidence: 99%
“…It has been reported to enhance the plant's resistance under waterlogging stress by enhancing the antioxidant enzyme system in tomato (Murshed et al, 2013), and in fruit trees such as mandarin (Sarkar et al, 2016). Research has shown that H 2 S can improve maize seed germination and seedling growth under high temperature by inducing antioxidant system and osmolyte biosynthesis (Zhou et al, 2018) and alleviate the damage to pea plants caused by waterlogging stress (Cheng et al, 2013). Application of H 2 S decreased the production of ROS in the plant leaves and roots by increasing antioxidant activities and had a protective role on plant growth, photosynthetic parameters, elements uptake under stress conditions (Ali et al, 2014a,b,c).…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous H 2 S, as well as donors such as sodium hydrosulfide (NaHS), can decrease Na + concentration to alleviate growth inhibition caused by NaCl stress in wheat seedlings [5]. NaHS induces the antioxidant system and osmolyte biosynthesis to improve the seed germination and seedling growth of maize under elevated temperatures [6]. Environmental stresses cause the accumulation of endogenous H 2 S, which regulates the peroxisomal H 2 O 2 metabolism, as a novel component in peroxisomes, by inhibiting catalase activity [7].…”
Section: Introductionmentioning
confidence: 99%